Knowledge sharing at government agency: case study at correspondence and archive section of Batam Indonesia free-zone authority/ Rayhan Musa Novian, Riche Cynthia Johan and Linda Setiawati - Novian, Rayhan Musa; Johan, Riche Cynthia; Setiawati, Linda (Faculty of Information Management, 2021)
Knowledge is an intangible asset that is important in organizations because the organization's competitive power can be developed by the knowledge of employees and groups in the organization. Organizational sustainability, which is increasingly complex and full of challenges in this ICT era, requires knowledge and skills to maintain the organization's continuity that is facing the challenges of the times. This study uses a qualitative method with a case study approach. To collect the data, the researcher used interviewing, observing, and documenting the study with data triangulation analysis to get comprehensive results. Researchers conducted interviews with five people who are employees at BIFZA. Researchers conducted participant observation and added to the study documentation. This research takes place in the BIFZA Correspondence and Archives Section. BIFZA is an institution established by the central government to manage land, investment, and free trade on the island of Batam. The results of this study show that knowledge sharing occurs naturally and has been well carried out in the Correspondence and Archives section, utilizing knowledge assets tacit and explicit using two sub-processes, namely socialization and exchange.